Rheology Behaviour of a Biopolymer Based on Chitosan-g-poly(Acrylamide-co-AcA) Hydrogels - Soleimani, Fatemeh; Sadeghi, Fatemeh; Sadeghi, Mohammad; Shasevari, Hadis; Soleimani, Arezoo; Sadeghi, Hossein (Asian Journal of Chemistry, 2012)
Acrylamide monomer was directly grafted onto chitosan using ammonium persulfate as an initiator and methylenebisacrylamide as a crosslinking agent under an inert atmosphere. Infrared spectroscopy and thermogravimetric analysis were carried out to confirm the chemical structure of the hydrogel. Moreover, morphology of the samples was examined by scanning electron microscopy. The rheology behavior of the synthesized hydrogels was preliminarily investigated with oscillating and rotational rheometer.